2020
DOI: 10.1002/14651858.cd013560
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant treatment for postnatal depression

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:To assess the effectiveness and safety of antidepressant drugs in comparison with any other treatment (psychological, psychosocial, or pharmacological), placebo, or treatment as usual for PND.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…3 PPD is preventable and treatable, and therefore, early identification of women at high risk is important to prevent or mitigate the detrimental consequences observed in relation to PPD. [4][5][6] Several risk factors for PPD have been identified and summarized in systematic reviews; however, having a relative with a psychiatric disorder is often not listed as a risk factor in reviews summarizing all identified risk factors. [7][8][9][10][11][12][13][14][15][16][17][18] Recently, 3 comprehensive umbrella reviews, compiling evidence from several systematic reviews on risk factors for PPD, also did not identify family history of psychiatric disorders as a risk factor.…”
mentioning
confidence: 99%
“…3 PPD is preventable and treatable, and therefore, early identification of women at high risk is important to prevent or mitigate the detrimental consequences observed in relation to PPD. [4][5][6] Several risk factors for PPD have been identified and summarized in systematic reviews; however, having a relative with a psychiatric disorder is often not listed as a risk factor in reviews summarizing all identified risk factors. [7][8][9][10][11][12][13][14][15][16][17][18] Recently, 3 comprehensive umbrella reviews, compiling evidence from several systematic reviews on risk factors for PPD, also did not identify family history of psychiatric disorders as a risk factor.…”
mentioning
confidence: 99%
“…Pharmacological treatment for PND is contraindicated mainly due to the issues of teratogenicity [15]. Fortunately, research on psychosocial interventions to treat PND and other common mental disorders has gained momentum in recent years [13], leading to innovations in screening, prevention, and treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…The treatment of PND also poses several challenges specific to the perinatal period [ 14 ]. Pharmacological treatment for PND is discouraged by perinatal women mainly due to concerns of teratogenicity [ 15 ]. Furthermore, there is a dearth of clinical trials on the effectiveness of antidepressants in the perinatal period due to ethical concerns [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacological treatment for PND is discouraged by perinatal women mainly due to concerns of teratogenicity [ 15 ]. Furthermore, there is a dearth of clinical trials on the effectiveness of antidepressants in the perinatal period due to ethical concerns [ 15 ]. The limited clinical trial evidence for antidepressants available has shown only small improvements in perinatal depressive symptoms, sometimes accompanied by side effects and poor adherence [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation